2020
DOI: 10.31219/osf.io/92u3m
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Bibliometric Analysis and Visualization of the Scientific Publications of Universities: A Study of Hamadan University of Medical Sciences during 1992-2018

Abstract: The evaluation of universities from different perspectives is important for their scientific development. Analyzing the scientific papers of a university under the bibliometric approach is one main evaluative approach. The aim of this study was to conduct a bibliometric analysis and visualization of papers published by Hamadan University of Medical Science (HUMS), Iran, during 1992-2018. This study used bibliometric and visualization techniques. Scopus database was used for data collection. 3753 papers were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 40 publications
(45 reference statements)
4
2
0
Order By: Relevance
“…In terms of international collaboration, it has been the most collaborative with researchers in the United States. The results of this section are consistent with the results of research by Swilleh et al (2014), Mokhtari et al (2019), Maharana and Sethi (2013). It seems that the United States has been very successful in attracting international collaboration, especially with universities of the desired level in different countries, and this has led to a steady improvement in the rankings of universities and journals in most ranking systems.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In terms of international collaboration, it has been the most collaborative with researchers in the United States. The results of this section are consistent with the results of research by Swilleh et al (2014), Mokhtari et al (2019), Maharana and Sethi (2013). It seems that the United States has been very successful in attracting international collaboration, especially with universities of the desired level in different countries, and this has led to a steady improvement in the rankings of universities and journals in most ranking systems.…”
Section: Discussionsupporting
confidence: 93%
“…The findings showed that in general, the process of scientific production of Alzahra University has been on the rise over time. These results are consistent with the findings of Mokhtari et al (2019). According to their findings, at the end of the last three years of the study, most scientific productions were reported.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations